The Effect of Balance Method and Local Point Acupuncture Therapy on Reducing Low Back Pain Scale at Sehat Bugar Acupuncture Bandung - Irsan Setiamukti; Nurtama Aditya Nugraha; Heni Nur Kusumawati (Indonesian Journal of Acupuncture, 2026)
Low Back Pain (LBP) is one of the most common musculoskeletal disorders experienced by many people and is a leading cause of decreased work productivity. To determine the effect of Balance Method acupuncture and local point acupuncture therapy on reducing the low back pain scale at Sehat Bugar Acupuncture Bandung. This study used a quasi-experimental method with a Pretest-Posttest Two Group Design. The total sample consisted of 30 respondents divided into two groups: the Balance Method therapy group and the local point therapy group. Each respondent received five acupuncture sessions with a frequency of twice per week. Pain intensity was measured using the Numeric Rating Scale (NRS) before and after treatment. Data were analyzed using the Independent Sample T-test. The results showed a significant decrease in pain scale in both groups (p < 0.050). This shows that both Balance Method and local point acupuncture therapies are effective in reducing low back pain scale, but the Balance Method therapy provides more optimal results.